(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The morphology of the placenta is very important in both singleton and multiple pregnancies. Determination of chorionicity, amniogenicity and identification of placental anomalies are key issues for the adequate management of multiple pregnancies. Placentas in dichorionic pregnancies were characterized by a higher incidence of maternal vascular lesions, whereas in monochorionic twins, the incidence of fetal vascular malperfusion and anomaly of umbilical cord attachment is high. Our analysis showed the percentage of occurrence of membrane attachment in monochorionic twins was 20.6%, and in dichorionic twins it was 10.2%. This results in unequal distribution of placental territory, which in turn can cause fetal growth discordance. Examination of the placenta after delivery can help evaluate the presence of placental and umbilical cord abnormalities, as well as provide with an information about chorion and imagination potential disease mechanisms affecting twin pregnancies.